Isolated and particularised - Picard, Robert G. (Javnost (Ljubljana), 2016)
The contemporary state of media and communications policy studies is disparate and incohesive because of the varying research backgrounds of its scholars, imprecise use of terms and lack of linkages to broader policy research. This article argues that there is a need for more consideration of the mechanisms and tools and of the institutional processes and practices of policy-making. The article argues that policy-making needs to be seen as a public sphere in which debate and compromise takes place, rather than an arena from which only one contestant can emerge - an approach that reduces the possibilities for reasoned debate, conciliation and cooperation. The article argues that the lack of this approach leads to normative intransigence, policy drift and protectionism that actually reduce the ability to pursue democratic and culture values in media and communications policy-making.
Keywords: Communication policy; Komunikacijska politika; Mass media; Mass media policy; Medijska politika; Množični mediji; Regulacija; Regulation